2003
DOI: 10.1128/iai.71.3.1569-1573.2003
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6-Deficient Mice Are Highly Susceptible toGiardia lambliaInfection but Exhibit Normal Intestinal Immunoglobulin A Responses against the Parasite

Abstract: In the present study, interleukin-6 (IL-6)-deficient mice were infected with Giardia lamblia clone GS/M-83-H7. Murine IL-6 deficiency did not affect the synthesis of parasite-specific intestinal immunoglobulin A. However, in contrast to wild-type mice, IL-6-deficient animals were not able to control the acute phase of parasite infection. Reverse transcription-PCR-based quantitation of cytokine mRNA levels in peripheral lymph node cells exhibited a short-term up-regulation of IL-4 expression in IL-6-deficient m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 23 publications
3
65
0
Order By: Relevance
“…In fact, a lower activation or damage to host cell should be associated with a low inflammation that progresses in giardiasis. Previous work using mouse models to determine the role of various cytokines in immunity to Giardia have shown that IL-6 plays a critical role in the control of primary infections with this parasite (Bienz et al, 2003;Zhou et al, 2003). Here, we have analysed whether MVs release by trophozoites should alter dendritic cells, which are a family of professional antigen-presenting cells (APCs), that reside in all peripheral tissues in an immature state, capable of antigen uptake and processing.…”
Section: Microvesicles From Giardia Intestinalis Modulate Dendritic Cmentioning
confidence: 99%
“…In fact, a lower activation or damage to host cell should be associated with a low inflammation that progresses in giardiasis. Previous work using mouse models to determine the role of various cytokines in immunity to Giardia have shown that IL-6 plays a critical role in the control of primary infections with this parasite (Bienz et al, 2003;Zhou et al, 2003). Here, we have analysed whether MVs release by trophozoites should alter dendritic cells, which are a family of professional antigen-presenting cells (APCs), that reside in all peripheral tissues in an immature state, capable of antigen uptake and processing.…”
Section: Microvesicles From Giardia Intestinalis Modulate Dendritic Cmentioning
confidence: 99%
“…It is unclear what immune mechanisms are responsible for effective control of infections (2,3). Although IgA has been shown to have a role in controlling infections (4), it is clear that IgA-independent mechanisms are also able to eliminate Giardia and that IL-6 appears to be pivotal for these pathways (5)(6)(7).…”
mentioning
confidence: 99%
“…As a consequence, blockade of IL-6 or IL-6 signaling has a profound impact on innate and acquired immune responses. Impaired IL-6 function causes enhanced susceptibility of mice to infection with various pathogens (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) but also results in protection in several mouse models for chronic inflammatory diseases (16)(17)(18). Not surprisingly, IL-6 signaling is also an important target of intervention in chronic inflammatory human diseases such as rheumatoid arthritis and Crohn's disease (19).…”
mentioning
confidence: 99%